PENERAPAN MODEL PROJECT BASED LEARNING DALAM MENULIS TEKS NEGOSIASI PADA PERKULIAHAN PENGEMBANGAN KETERAMPILAN MENULIS - Stella Talitha; Rina Rosdiana (Pedagonal : Jurnal Ilmiah Pendidikan, 2020)
APPLICATION OF PROJECT BASED LEARNING MODEL IN WRITING NEGOTIATION TEXT IN DEVELOPMENT OF WRITING SKILLS LECTUREAbstract.  This research is based on the application of the Project Based Learning (PjBL) model on negotiating text learning. Through this model, students are asked to work on negotiating video projects and write negotiating texts. This study aims to describe: (1) the development of Project Based Learning (PjBL) models in negotiating text learning, (2) the ability to make negotiating videos, and (3) the ability to write negotiating texts of fourth semester students of the Indonesian Language and Literature Education Study Program, FKIP, Pakuan University, Bogor. The ability of students to make videos is assessed based on the characteristics of the video as a learning medium. The videos collected were eight videos according to the group formed. Characteristics assessed in video media include: (1) message clarity, (2) content representation, (3) visualization with media, 4) uses a high quality resolution, (5) and can be used classically or individually. From the 8 student groups that have been formed, 6 of them chose and made a video negotiation with electronic topics with a percentage of 75% and 2 groups of students choose and make a video negotiation with automotive topics with a percentage of 25%. Students ability to write negotiating text has an average of 84.61 which falls into good category. From 26 students, 9 of them included in the excellent category with a percentage of 34.61%, 12 of them included in the good category with a percentage of 46.15%, and 5 of them included in the plenty category with a percentage of 19.24%. This shows the ability of students to write negotiating texts based on the negotiation videos they have made is good.